2018
DOI: 10.1177/0885328218812487
|View full text |Cite
|
Sign up to set email alerts
|

In vitro performance of a nanobiocomposite scaffold containing boron-modified bioactive glass nanoparticles for dentin regeneration

Abstract: Every year, many dental restoration methods are carried out in the world and most of them do not succeed. High cost of these restorations and rejection possibility of the implants are main drawbacks. For this reason, a regenerative approach for repairing the damaged dentin-pulp complex or generating a new tissue is needed. In this study, the potential of threedimensional cellulose acetate/oxidized pullulan/gelatin-based dentin-like constructs containing 10 or 20% bioactive glass nanoparticles was studied to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 78 publications
0
21
0
Order By: Relevance
“…In another study, a gradual release of B from B‐containing mesoporous BG scaffolds enhanced proliferation of osteoblasts (Wu et al, ). We previously also observed the positive effect of B‐doped BG on proliferation of hDPSCs (Moonesi Rad et al, ; Moonesi Rad et al, ; Moonesi Rad et al, )…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In another study, a gradual release of B from B‐containing mesoporous BG scaffolds enhanced proliferation of osteoblasts (Wu et al, ). We previously also observed the positive effect of B‐doped BG on proliferation of hDPSCs (Moonesi Rad et al, ; Moonesi Rad et al, ; Moonesi Rad et al, )…”
Section: Discussionmentioning
confidence: 67%
“…Additionally, it has been reported that B addition enhanced the osteogenic and odontogenic differentiation potential of dental stem cells (Demirci et al, ; Taşlı, Doğan, Demirci, & Şahin, ). In our previous study, positive effect of B‐modified bioactive glass nanoparticles (BG‐NPs) on odontogenic differentiation of hDPSCs was observed (Moonesi Rad et al, ; Moonesi Rad Atila et al, ; Moonesi Rad et al, )…”
Section: Introductionmentioning
confidence: 99%
“…Antibacterial and angiogenic properties and excellent bioactivity of nBGs have made them as a suitable candidate for dentin regeneration applications. Incorporation of boron modified nBGs in the cellulose acetate/oxidized pullulan/gelatin-based constructs has shown promising results for dentin regeneration through increase in cellular viability, Intracellular calcium deposition (ICD) and ALP activity while keeping the boron ion released below toxic level (Moonesi Rad et al, 2019). Rad et al demonstrated that incorporation of 6.25 mg/ml boron doped nBGs into cell culture media has increased the ALP activity and ICD.…”
Section: Ceramic Nanoparticlesmentioning
confidence: 99%
“…De-novo presence of obturating material rich of Ca and P compounds on one hand and the visual proof of obliteration on the other hand seems rather close to the original idea of bioglass-related regeneration that has been described for bioglass use, originally in bone [37]. For dentin, bioglass-based materials have so far been reported to show regenerative potential if used as experimental resin based adhesive on dentin discs [38] or in a three-dimensional scaffold in-vitro [39]. In principle, obturation material in dentin tubules, as observed in the present experiment, may derive from different origin: Ca and P components might derive from dentin of the tubular walls.…”
Section: Discussionmentioning
confidence: 64%
“…In combination with the applied simulated pulp pressure, the set-up was intended to mimic a worst-case scenario, with wide open lumina and pulp liquid fluid flow in the opposing direction, the penetration of the tested desensitizer might be more difficult than in any clinical situation. This might also explain the fact that the penetration depth of the tested bioglass product was considerably lower than in another in-vitro study on a similar bioglass-based desensitizer: Moonesi et al [39] reported penetration depth of 3.5–25 μm in different settings and application times. In a previous study on DentinoCer, a considerably deeper obturation of the tubules (20–100 μm) was reported [28].…”
Section: Discussionmentioning
confidence: 73%